2021
DOI: 10.1002/slct.202101683
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Spherical Cellulose Nanoparticles from Recycled Waste Cotton for Anticancer Drug Delivery

Abstract: Using natural waste resources as a starting material for the preparation of cellulose nanoparticles is a field of interest for novel pharmaceutical applications. This study aims to introduce cellulose nanoparticles for Doxorubicin (DOX) delivery to tumor cells. Cellulose nanocrystals were first produced from waste cotton by hydrochloric acid (1 M) hydrolysis, and then spherical cellulose nanoparticles were prepared by microemulsion method. The prepared particles were spherical with 300 nm in size, and the zeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Spherical nanocarriers come in various shapes, from micellar to vesicular, which include internal structures with a hollow center and two continuous layers. 80 Barua et al reported higher non-specific cellular uptake of polystyrene (PS)-based nano-spheres by breast cancer cells (BT-474, SK-BR-3, and MDA-MB-231) compared with their nanorod and disc counterparts. 81 However, after covering them with the monoclonal antibody trastuzumab, it was shown that nanorods were more capable of being taken up by cells than spheres or discs.…”
Section: Classification Of Drug Carriers Based On Morphologymentioning
confidence: 99%
“…Spherical nanocarriers come in various shapes, from micellar to vesicular, which include internal structures with a hollow center and two continuous layers. 80 Barua et al reported higher non-specific cellular uptake of polystyrene (PS)-based nano-spheres by breast cancer cells (BT-474, SK-BR-3, and MDA-MB-231) compared with their nanorod and disc counterparts. 81 However, after covering them with the monoclonal antibody trastuzumab, it was shown that nanorods were more capable of being taken up by cells than spheres or discs.…”
Section: Classification Of Drug Carriers Based On Morphologymentioning
confidence: 99%